Enhancing stakeholder engagement: Using the communication perspective to identify and enhance stakeholder communication in place management - Emira Limani; Labinot Hajdari; Blerim Limani; Judita Krasniqi (Cogent Business & Management, 2024)
The purpose of this paper is to create a model based on a dialogical approach among city branding stakeholders using the Coordinated Management of Meaning (CMM) framework. This study combines conceptual and theoretical frameworks with a case study to explore how the dialogical approach enhances coordination among stakeholders. The findings reveal that integrating CMM's communication perspective into stakeholder analysis provides a deeper understanding of stakeholder communication and city branding strategies. This approach, which includes shared meaning, coordinated actions, and contextual interpretation within stakeholder mapping, results in an easily applicable communication model for multiple stakeholders involved in city branding initiatives. The paper also offers practical steps for initiating and coordinating dialogue among stakeholders. Furthermore, this paper contributes to the field by expanding on stakeholder mapping based on relevant pillars for place branding and utilizes a case study to illustrate a dialogical approach by demonstrating the value of applying CMM for effective place management processes.
Keywords: 650; Stakeholder mapping; coordinated management of meaning; place management; communication; dialogical approach